The "New" Theory of Consumer Demand and Monopolistic Competition - Archibald, G. C.; Rosenbluth, G. (Quarterly Journal of Economics, 1975)
I. Introduction, 569. — II. Definition of the group, 570. — III. Demand conditions — the two-characteristics case, 573. — IV. The case of three characteristics, 576. — V. Four or more characteristics. 581. — VI. Cost conditions, 584. — VII. Entry and equilibrium, 586. — VIII. Further implications, 587. — IX. Conclusion, 589.